Contemporary Use of Traditional and Imported Food among Greenlandic Inuit - Pars, Tine; Osler, Merete; Bjerregaard, Peter (ARCTIC, 2001)
A health interview survey was carried out in Greenland in 1993-94 among randomly selected adult Inuit (N = 1580) to gather information about people's perceptions of their own health and living conditions. Questions about preference for and frequency of consumption of selected traditional and imported food items were included in the questionnaire. Preference ratings show that traditional food was well liked in all age groups, but especially by the elders. The questionnaire showed more pronounced differences between age groups in how frequently traditional foods were consumed. Residence in a village or a remote part of the country, male gender, and a trditional upbringing were also good predictors of a high consumption of traditional food. On average, seal meat was the most frequently consumed traditional food, eaten daily by 20% of respondents, followed by fish (17%), wildfowl (10%), whale meat (6%), and terrestrial animals (2%). Imported food items like potatoes, cheese, and fruit syrup were consumed daily by more than 70%. Two concerns for the future are the decreasing consumption of traditional food among the younger generations and the possible contribution of contaminants in traditional food to this trend. Une enquête par entrevue sur la santé a été menée au Groenland en 1993-1994 parmi des Inuits adultes (N = 1580) pris au hasard, afin de collecter de l'information sur la perception qu'avaient les gens de leur propre santé et de leurs conditions de de leur consommation. Les taux de préférence montrent que les aliments traditionnels étaient très appréciés dans tous les groupes d'âges, mais surtout par les aînés. Le questionnaire révélait des différences plus nettes entre les groupes d'âges quant à la fréquence à laquelle les aliments traditionnels étaient consommés. Le fait d'habiter un village ou une région reculée du pays, l'appartenance au sexe masculin et une éducation traditionnelle étaient également de bons paramètres de prévision d'une grande consommation d'aliments traditionnels. En moyenne, la ...